Reconceptualization of Diversion Governance in Juvenile Justice Systems: A Restorative Justice Approach to Prison Overcrowding Reduction in Indonesia - Muslim Mubarrok; Ismail Koto (Yayasan Abdurrauf Cendekia Nusantara, 2026)
The increasing number of children in conflict with the law in Indonesia has not been matched by the optimal implementation of non-litigation mechanisms, thereby contributing to the problem of overcrowding in juvenile correctional institutions. Although diversion has been formally adopted within the juvenile justice system, its implementation remains limited and inconsistent across different stages of the judicial process. This study aims to analyze the reconceptualization of diversion as a restorative justice instrument to reduce overcrowding in juvenile correctional facilities in Indonesia. This research employs a normative legal method with statutory and conceptual approaches, supported by an analysis of relevant legal frameworks and scholarly literature on juvenile justice systems. The findings reveal that the implementation of diversion faces structural constraints, particularly its limited application at certain stages of the judicial process, lack of coordination among law enforcement agencies, and the persistence of a retributive paradigm in legal practice. As a result, diversion has not been fully effective in reducing the number of children entering correctional institutions, and the issue of overcrowding remains unresolved. This study highlights the need for a reconceptualization of diversion governance that is more integrative and grounded in restorative justice principles, by strengthening the roles of all stakeholders within the juvenile justice system. The contribution of this research lies in developing a conceptual framework positioning diversion as a systemic strategy for sustainable reform of juvenile justice, particularly in addressing prison overcrowding in Indonesia. [Peningkatan jumlah anak yang berhadapan dengan hukum di Indonesia tidak diimbangi dengan optimalisasi mekanisme penyelesaian non-litigasi, sehingga berkontribusi terhadap permasalahan overcrowding pada lembaga pemasyarakatan. Meskipun konsep diversi telah diadopsi dalam sistem peradilan pidana anak, implementasinya masih cenderung terbatas dan belum konsisten pada setiap tahapan proses peradilan. Penelitian ini bertujuan untuk menganalisis rekonseptualisasi diversi sebagai instrumen keadilan restoratif dalam mengurangi overcrowding lembaga pemasyarakatan anak di Indonesia. Penelitian ini menggunakan metode hukum normatif dengan pendekatan perundang-undangan dan konseptual, yang didukung oleh analisis terhadap berbagai regulasi serta literatur terkait sistem peradilan pidana anak. Hasil penelitian menunjukkan bahwa implementasi diversi masih menghadapi kendala struktural, terutama keterbatasan penerapan pada tahap tertentu dalam proses peradilan, kurangnya koordinasi antar aparat penegak hukum, serta dominannya paradigma retributif dalam praktik penegakan hukum. Kondisi ini menyebabkan diversi belum optimal dalam menekan jumlah anak yang masuk ke lembaga pemasyarakatan, sehingga permasalahan overcrowding tetap berlangsung. Penelitian ini menegaskan bahwa diperlukan rekonseptualisasi tata kelola diversi yang lebih integratif dan berbasis keadilan restoratif, dengan memperkuat peran semua aktor dalam sistem peradilan pidana anak. Kontribusi penelitian ini terletak pada pengembangan kerangka konseptual mengenai diversi sebagai strategi sistemik dalam reformasi peradilan pidana anak, khususnya dalam mengatasi overcrowding secara berkelanjutan di Indonesia.]